Stuck in the Experience: How Tiktok Shop Leverages Perceived Interactivity, Immersion, and Enjoyment in Purchase Decisions - Nisrina Hamid; Indri Hapsari; Sri Wani (Jurnal Manajemen dan Kewirausahaan, 2024)
Initially a social media platform, TikTok has evolved into the most extensively downloaded medium for product promotion and sales, prompting both endorsement and critique. This study aims to explore the impact of enjoyment as a mediating variable between perceived interactivity, immersion, and buying decisions utilizing SEM-PLS analysis. Findings reveal that perceived interactivity and immersion significantly and positively influence enjoyment, yet perceived interactivity fails to significantly impact purchase decisions positively. Notably, enjoyment as a mediating variable demonstrates mediating effects on purchase decisions, with distinct degrees of mediation, including partial and full mediation.